Design of QFT controller for a bench-top helicopter system model - Mansor, Hasmah; Zaeri, Amir Hossein; Mohd Noor, Samsul Bahari; Raja Ahmad, Raja Kamil; Taip, Farah Saleena; Ali, Hazem Ibrahim (UK Simulation Society, 2010)
Quantitative Feedback Theory (QFT) technique is a robust control design based on frequency domain methodology. It is useful for practical design of feedback system in ensuring plant’s stability by reducing the sensitivity to parameter variation and attenuate the effect of disturbances. Parameter variation or physical changes to the plant is taken into account in the QFT controller’s design. This paper will discuss on QFT control design methodology and will work on a case study; laboratory scale plant of a bench-top helicopter. The bench-top helicopter is very difficult to control due to its non-linear behavior and subject to parameter variation. By using QFT controller, a full operational envelop design is achieved according to pre-defined specifications. The proposed method is compared with the conventional PI controller. The obtained simulation results show QFT controller is more efficient and robust than the PI controller.